Farm Size, Cropping Pattern and Productivity Variation in Punjab: The Analysis of Mansa and Jalandhar Districts - Singh, Jagdeep; yadav, Hanuman Singh (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
The present paper analyzes the trend and patterns of farm size, productivity and cropping pattern in districts of Mansa and Jalandhar. The results show that medium and large holdings are increasing in number over the time in both the districts. Increase in size of holdings coupled with other factors like increase in productivity in limited number of crops, minimum support price for wheat and rice as well as higher possibility of use of modern technology in wheat and rice cultivation has lead to wheat rice cycle. The other crops like cotton, maize, potato etc. are more popular among marginal and small farmers. It may be due to easy availability of family labour. Overall, the study points towards specialization in the cropping pattern, stagnation in productivity growth and increasing size of operational holdings.